2017
DOI: 10.1371/journal.pone.0184428
|View full text |Cite
|
Sign up to set email alerts
|

Use of alcohol and drugs with addiction potential among older women and men in a population-based study. The Nord-Trøndelag Health Study 2006-2008 (HUNT3)

Abstract: BackgroundLittle is known about the consumption habits of older adults in Norway with respect to alcohol and the use of drugs with addiction potential, such as benzodiazepines, z-hypnotics and opioids, among regular drinkers. We studied the prevalence of self-reported consumption of alcohol on a regular basis in community-living older men and women (≥ 65 years). Furthermore, we investigated the prevalence of dispensed prescribed drugs with addiction potential in older men and women who were regular drinkers.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 53 publications
3
19
3
7
Order By: Relevance
“…Older men with chronic conditions may be more likely than women to combine the use of alcohol and drugs with addiction potential [37]. However, in a previous study we found that a higher proportion of older women (39.6%) than men (22.8%) who were regular drinkers (alcohol consumption ≥ 1 day a week) also used drugs with addiction potential [38]. Thus, it seems that both older women and men may use alcohol in addition to drugs with addiction potential [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Older men with chronic conditions may be more likely than women to combine the use of alcohol and drugs with addiction potential [37]. However, in a previous study we found that a higher proportion of older women (39.6%) than men (22.8%) who were regular drinkers (alcohol consumption ≥ 1 day a week) also used drugs with addiction potential [38]. Thus, it seems that both older women and men may use alcohol in addition to drugs with addiction potential [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous study we found that a higher proportion of older women (39.6%) than men (22.8%) who were regular drinkers (alcohol consumption ≥ 1 day a week) also used drugs with addiction potential [38]. Thus, it seems that both older women and men may use alcohol in addition to drugs with addiction potential [38]. Nevertheless, we did not find an association in men or women between a possible combination of frequent drinking and use of prescribed drugs with addiction potential and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence of risky alcohol consumption doubled from HUNT2 (1995-97) to HUNT3 (2006-08) for men and women over 60 years [18]. 28.2% participants aged 65 years and older reported drinking alcohol once or more weekly in HUNT3 [44]. In 2019 38% of 45-66-year-old Norwegians reported drinking alcohol once or more weekly; higher among older adults and men compared with women [45].…”
Section: Discussionmentioning
confidence: 99%